2011
DOI: 10.5897/ajb10.1676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus and potassium on seed production of berseem

Abstract: 1) and thousand seed weight (1.90g) were obtained from plots having no fertilizers (control or 0 kg ha -1 ).The findings of this study shows that berseem had better performance in terms of seed production when fertilized with of 60 kg P ha -1 and 30 kg K ha -1 in irrigated areas of Peshawar valley.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…Moreover, the increases in vegetative growth lead to heavier seeds (weight of 1000 seed). These results are in harmonious with those reported by Beena et al (2011) on berseem and Thalooth et al (2006) on mungbean and Aboelgoud et al (2015) on multi-cut berseem variety " Serw 1 " . Such enhancement effect could be attributed to the favorable effect of this nutrient on metabolism and biological activity and its stimulating affection photosynynthetic pigments and enzyme activity which in turn increase vegetative growth traits of plants (Tausz et al, 2004).…”
Section: Seed Yield and Its Componentssupporting
confidence: 91%
“…Moreover, the increases in vegetative growth lead to heavier seeds (weight of 1000 seed). These results are in harmonious with those reported by Beena et al (2011) on berseem and Thalooth et al (2006) on mungbean and Aboelgoud et al (2015) on multi-cut berseem variety " Serw 1 " . Such enhancement effect could be attributed to the favorable effect of this nutrient on metabolism and biological activity and its stimulating affection photosynynthetic pigments and enzyme activity which in turn increase vegetative growth traits of plants (Tausz et al, 2004).…”
Section: Seed Yield and Its Componentssupporting
confidence: 91%
“…These findings may be attributed to more branching capacity of berseem with more well filled heads. The same results were founded by Beena et al (2011) and (Paricha andBansal, 2002, andTiwari et al, 2003) they reported that as potassium is known to exert a special influence on formation and translocation of photosynthetic material, any deficiency of this element will lead to either shrunken or undersize seeds. As the potassium rates are raised, escalated translocation of photosynthate to the young forming seeds leads to formation of larger seeds.…”
Section: Weight Of Heads/msupporting
confidence: 60%
“…Meanwhile, the lowest number of heads/m 2 was observed in control treatments. The possible reason could be due to the fact that, there was more vegetative growth in berseem which leads to production of more heads (Beena et al, 2011).…”
Section: Number Of Heads/mmentioning
confidence: 99%
See 2 more Smart Citations